Light-sensitive monolayer-thick nanocrystal skins of face-down self-oriented colloidal quantum wells - Bozkaya, Taylan (2024)
Colloidal quantum wells (CQWs), a quasi-two-dimensional, atomically-flat sub-family of semiconductor nanocrystals, are well suited to produce excellent devices for photosensing applications thanks to their extraordinarily large absorption cross-sections. In this work, we propose and demonstrate a new class of light-sensitive nanocrystal skins (LS-NS) that employ a monolayer of face-down orientation-controlled self-assembled CQWs as the active absorbing layer in the UV-visible range. This CQW LS-NS platform enables non-conventional photosensing operation that relies on the strong optical absorption of the monolayered assembly of CQWs and the subsequent photogenerated potential build-up across the device, allowing for self-powered operation. Here such self-oriented CQWs reduce the surface roughness in their monolayer-thick film, essential to high device performance. Owing to their ease of fabrication and low cost, these devices hold great promise for large-scale use in semi-transparent photosensing surfaces.